European clinical practice guidelines for the definition, diagnosis, and treatment of oligometastatic esophagogastric cancer (OMEC-4) - Kroese, Tiuri E; Bronzwaer, Sebastiaan; van Rossum, Peter S N; Schoppman, Sebastian F; Deseyne, Pieter R A J; van Cutsem, Eric; Haustermans, Karin; Nafteux, Philippe; Thomas, Melissa; Obermannova, Radka; Mortensen, Hanna R; Nordsmark, Marianne; et al. (European journal of cancer, 2024)
INTRODUCTION: The OligoMetastatic Esophagogastric Cancer (OMEC) project aims to provide clinical practice guidelines for the definition, diagnosis, and treatment of esophagogastric oligometastatic disease (OMD). METHODS: Guidelines were developed according to AGREE II and GRADE principles. Guidelines were based on a systematic review (OMEC-1), clinical case discussions (OMEC-2), and a Delphi consensus study (OMEC-3) by 49 European expert centers for esophagogastric cancer. OMEC identified patients for whom the term OMD is considered or could be considered. Disease-free interval (DFI) was defined as the time between primary tumor treatment and detection of OMD. RESULTS: Moderate to high quality of evidence was found (i.e. 1 randomized and 4 non-randomized phase II trials) resulting in moderate recommendations. OMD is considered in esophagogastric cancer patients with 1 organ with ≤ 3 metastases or 1 involved extra-regional lymph node station. In addition, OMD continues to be considered in patients with OMD without progression in number of metastases after systemic therapy. 18F-FDG PET/CT imaging is recommended for baseline staging and for restaging after systemic therapy when local treatment is considered. For patients with synchronous OMD or metachronous OMD and a DFI ≤ 2 years, recommended treatment consists of systemic therapy followed by restaging to assess suitability for local treatment. For patients with metachronous OMD and DFI > 2 years, upfront local treatment is additionally recommended. DISCUSSION: These multidisciplinary European clinical practice guidelines for the uniform definition, diagnosis and treatment of esophagogastric OMD can be used to standardize inclusion criteria in future clinical trials and to reduce variation in treatment.
Keywords: metastázy nádorů; Stomach Neoplasms; Evropa; Neoplasm Metastasis; delfská metoda; Humans; Delphi Technique; Consensus; Europe; nádory jícnu; lidé; konsensus; Esophageal Neoplasms; nádory žaludku